Direct Z-scheme MgIn2S4/TiO2 heterojunction for enhanced photocathodic protection of metals under visible light. (28th January 2022) - Li, Hong; Cui, Xingqiang; Song, Weizhe; Yang, Zhanyuan; Li, Yanhui; Zhang, Pengfei; Zheng, Zongmin; Wang, Yuqi; Li, Junru; Ma, Fubin
Abstract: To improve the photocathodic protection performance of traditional TiO2 photoanodes for metals, constructing a Z-scheme heterojunction is one of the most promising and creative strategies. Herein, we fabricated a novel Z-scheme MgIn2 S4 nanosheets/TiO2 nanotube nanocomposite through anodization and hydrothermal method. The optimized Z-scheme MgIn2 S4 /TiO2 nanocomposites exhibited stronger visible light absorption, higher separation efficiency of photoelectrons and photocathodic protection performances in comparison to pure TiO2 . The theoretical analysis and experimental results show that the Z-scheme heterojunction and oxygen vacancies jointly improved the separation efficiency of photogenerated electron–hole pairs and visible light absorption capacity, thereby improving the photoelectric conversion performance of the MgIn2 S4 /TiO2 nanocomposites. Furthermore, the influence of the precursor solution concentration on the photocathodic protection performances of the composites was investigated. As a result, when the concentration of magnesium source in the precursor solution was 0.06 mmol, the prepared MgIn2 S4 /TiO2 -0.06 displayed the best photocathodic protection performance. In addition, the hydroxyl radicals (·OH) generated in the electron spin resonance (ESR) experiment verified the Z-scheme heterojunction mechanism of the MgIn2 S4 /TiO2 composite, and also demonstrated the excellent redox performance of the composite. This work provides valuable reference for the construction of high-performance Z-scheme heterojunctions for photocathode protection of metals.